Dilema Birokrasi Dalam Democratic Governance - I Wayan Winarsa (Universitas Mahendradatta Denpasar, 2020)
State / public management that is clean from corruption, collusion, nepotism, and management of state / public resources must be transparent, open, more than that every citizen is given access to participate in influencing the management of the way — participation. Public agencies need to be monitored, for example by Transparency Inter- national for global coverage or Indonesian Corruption Watch for national coverage. Now we have known a lot of “watchdog dogs” like that, including those covering the district / city or even village / village. Good governance is thus synonymous with transparency and participation - democratic governance. This includes the rule of law (rechtsstaatlichkeit and Berechenbarkeit). In approximately 1990 or the late 1980s the World Bank conclud- ed, that anything and any “donations” disbursed to African countries (Sub-Saharan) must be exhausted without a trace. Just like water poured over a hot desert. This phenomenon is referred to by the World Bank as bad governance, meaning poor management (money, resources). This is euphemism for, especially if it’s not corruption.